Avaliação da aprendizagem e ética da responsabilidade no ensino médio: a perspectiva docente na dinâmica de sentidos da teoria e da prática - Mota, Cinthya Raquel Pimentel da (2023)
Assesment in education assumes improvements in the teaching and learning process and is presented as a cycle for the basic understanding of knowledge, whether of humans orn ature. This research presentes itself as a proposal for conceptualized by the philosopher Hans Jonas, in a way to raise significant propositions for the transformation o four Society, with the objective of analyzing meanings that underlie the momento f learning evaluation, based on a responsible ethics in the dynamics of meanings of theory and practice in high school at the Federal Institute of Education, Science and Tecnology of Paraíba advanced campus Cabedelo Centro, as well as specific objectives: observe the assigned descripitions by teachers in relation to the concepts, methodologies, strategies and instruments of learning assessment; understand how teachers use their theoretical knowledge about learning assessment with everyday practices in the classroom; and analyze implications of responsible ethics in the evaluation process for the achievement of significant learning. For the development o four research, we will use the assumptions of the qaulitative research approach, based on the epistemologival paradigma of Phenomenology. Documentary analysis, observation and interviews were used as data collection techniques, and the assumptions of the phenomenologival method were used for data analysis. We will resort to this type of research, given the need to understand the contexts, listen to the respondentes, respecting their singularities. Our aim to contribute to the construction and improvement of new knowledge about the subject, so that it can raise new reflections and new studies, thus being extremely relevant at the presente time, as we believe that the practice of evaluation articulated with the principles of ethics in responsibility constitutes a starting point for significant changes and transformations for education and also for Society, contributing to the teach9ing and learning process. At the endo f this thesis, we emphasize the importance of reflecting on new public policies that directly affect the teaching and learning process, in which, based on the principles of the ethics of responsibility, it is possible to predict the bonum or malum for the future of Society and thus think changes in attitufes and postures that make human survival possible.